Gender role differentiation in household fuel transition decision-making: Implications for education and training in Uganda - Elasu, Joseph; Ntayi, Joseph Mpeera; Adaramola, Muyiwa S.; Buyinza, Faisal; Ngoma, Muhammad; Atukunda, Ronnette (Frontiers in Sustainability, 2023)
Introduction The role of gender and gender role differentiation has been of long standing interest and has remained a concern regarding the access and use of energy fuels for cooking in households. Although there seems to be a thin line between gender. However, studies on gender role differentiation in household fuel transition have framed gender as the biological construction of male and female rather than social roles. Methods This study used A multinomial probit regression model (MNP) to analyze the effect of gender role differentiation on household transition decisions from high to low-polluting fuels and their implications on education and training in Uganda. The study used the National Household Survey data collected by Uganda Bureau of Statistics. Findings and discussion The findings revealed that the gender role differentiation significantly affected household fuel transition decisions. The study concludes by highlighting the implications of such gender role differentiation on education and training in Uganda.